Effects of different application rates of organic fertilizer on growth, physiology and antioxidant activity of sambung nyawa (Gynura procumbens) - Mohammad Yusoff, Martini; B., Mohamad Faiz; Megat Wahab, Puteri Edaroyati; Misran, Azizah (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Gynura procumbens (Lour) Merr. or locally known as sambung nyawa is one of the herbal plants which has been recognized in the Agricultural National Key Economic Areas (NKEA). Currently, G. procumbens plants are cultivated in small scale by farmers with little guidance on improved management practices. It is important to have appropriate agronomic practices of this herbal plant such as fertilization to maximize its yield and quality. However, there is no documented information on fertilization practices for large scale cultivation of G. procumbens in Malaysia. Thus, this study was conducted to determine the effects of different rates of organic fertilizer by using vermicompost on growth, physiology and secondary metabolite content of G. procumbens. Five different rates of nitrogen (0, 100, 200, 300 and 400 kg N ha-1) were applied to G. procumbens grown in an open field at Faculty of Agriculture, Universiti Putra Malaysia. Significant effects of 100 to 200 kg N ha-1 of organic fertilizer on plant height, leaf fresh and dry weight, number of branches and leaf area index were detected with increased rates of organic fertilizer rates, but were lower when subjected to 300 to 400 kg N ha-1. Relative chlorophyll content was highest when treated with 400 kg N ha-1 of organic fertilizer. Potassium concentration in the leaves of G. procumbens was increased when subjected to 100 kg N ha-1 of organic fertilizer. Antioxidant activity using DPPH method in the leaves of G. procumbens was highest at 100 kg N ha-1. In conclusion, 100 to 200 kg N ha-1 is an optimum range of organic fertilizer for maximum growth and yield of G. procumbens.